Evaluating the long-term storage of Cryphonectria parasitica - Joshua C. Springer; Anita L. Davelos Baines; Matthew T. Chansler; Andrew M. Jarosz (Fungal Genetics Reports, 2013)
Isolates of the Chestnut blight pathogen, Cryphonectria parasitica, from six populations in Michigan, were stored in the late 1990s as agar plugs of mycelium in vials of sterile water held at room temperature. Approximately 29% of the fungal isolates were infected with mycoviruses at the time of storage. Each isolate was tested for revivification effectiveness by taking aliquots from vials filled with agar plugs of C. parasitica and sterile water and plating onto potato dextrose agar. Average revivification success was 70.5% across populations with a range of 33—84% within populations. In situations where vials had dried out during storage, success was low (4%), while success for vials that retained sterile water averaged 90%. Most importantly however, is the loss of mycoviruses from stored isolates; only 2 of 119 stored mycovirus infected isolates still contained mycoviruses after storage, suggesting that the double-stranded RNA mycoviruses are degraded during storage.